OXYGEN DEFICIENT SNO2(110) AND TIO2(110) - A COMPARATIVE-STUDY BY PHOTOEMISSION - Egdell, R; Eriksen, S; Flavell, W (1986)
Oxygen deficient SnO2 (110) and TiO2 (110) surfaces prepared by argon ion bombardment of stoichiometric crystals have been studied by He(I) photoemission spectroscopy. On TiO2 (110), 3d1 polaronic states localised at crystallographic shear planes give rise to a band peaking 1 eV below the Fermi level. By contrast for SnO2 (110) there is strong 5s-5p hybridisation that pushed the Sn2+ lone-pair-like defect state down toward the valence band edge. © 1986.